2020
DOI: 10.1007/s00167-020-05845-5
|View full text |Cite
|
Sign up to set email alerts
|

Ligament stabilization improved clinical and radiographic outcomes for individuals with chronic ankle instability and medial ankle osteoarthritis

Abstract: Purpose Chronic ankle instability with a long symptom duration is often accompanied by medial compartment ankle osteoarthritis (OA). However, the outcomes of individuals after ligament stabilization have rarely been reported. The radiographic and clinical outcomes after ligament stabilization in individuals with chronic ankle instability and medial compartment OA were investigated. Methods The study investigated 27 ankles with chronic ankle instability and medial compartment OA that underwent lateral ankle lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Patients with ankle instability often present with concurrent OLT, with a reported incidence of up to 60% to 95%. 30,33 In a recently published study, Kim et al 20 showed that patients with chronic ankle instability and medial ankle osteoarthritis significantly benefit from LLS, with AOFAS scores increasing from 61.9 ± 14.2 to 89.7 ± 6.2 (P < .001) postoperatively. Conversely, Jiang et al 19 investigated whether concurrent arthroscopic OLT treatment with abrasion, curettage, drilling, or microfracture has an adverse effect on the clinical outcome of LLS in patients with chronic ankle instability, as it might compromise the rehabilitation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ankle instability often present with concurrent OLT, with a reported incidence of up to 60% to 95%. 30,33 In a recently published study, Kim et al 20 showed that patients with chronic ankle instability and medial ankle osteoarthritis significantly benefit from LLS, with AOFAS scores increasing from 61.9 ± 14.2 to 89.7 ± 6.2 (P < .001) postoperatively. Conversely, Jiang et al 19 investigated whether concurrent arthroscopic OLT treatment with abrasion, curettage, drilling, or microfracture has an adverse effect on the clinical outcome of LLS in patients with chronic ankle instability, as it might compromise the rehabilitation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Osteophytes form around the ankle when the joint is unstable for an extended period of time [ 21 ]. Walsh et al performed arthroscopic treatment only for anterior ankle impingement and discovered that up to 84% had recurrence of osteophytes on imaging during the 5-year follow-up, which is thought to be associated with failure to restore ankle stability [ 6 ]. Yang et al, on the other hand, used ankle arthroscopy to stabilize the ankle joint with modified Broström repair of lateral ankle ligaments and to resect the anterior ankle osteophytes concurrently, and there was no osteophytes recurrence at a mean 3-year follow-up [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anterior talofibular ligament (ATFL), calcaneofibular ligament (CFL), and posterior talofibular ligament (PTFL) make up the lateral ankle ligament complex, which is one of the most critical structures for maintaining lateral ankle stability [ 4 , 5 ]. The majority of CLAI patients who follow conservative treatment may effectively manage their instability; however, for those who do not respond to conservative treatment, lateral ankle ligament complex repair/reconstruction is frequently recommended [ 6 ]. It is worth mentioning that the ATFL is the most commonly injured ligament structure, and in some cases, the only one [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was approved by the Peking University Third Hospital Medical Science Research Ethics Committee (IRB00006761‐M2019035). CLAI with mechanical instability was diagnosed clinically when the patient met all of the following criteria [11, 18, 25]: (1) A traumatic history of at least one significant ankle sprain; (2) persistent clinical symptoms including pain, swelling, ‘giving way’ sense, feeling of instability or recurrent sprain for at least 3 months; (3) physical examinations, including ankle anterior drawer test and varus stress test, confirmed grade III joint laxity; (4) radiographic findings with attenuated, scarred, wavy or defective lateral ankle ligaments on MRI. Respective anatomic reconstruction and MBG procedure were performed based on the quality of the ligament remnant.…”
Section: Methodsmentioning
confidence: 99%
“…Acute ankle sprain, as one of the most common sports‐related injury, usually calls for conservative treatment first [2]. However, 10–30% of patient developed chronic lateral ankle instability (CLAI), which requires ankle stabilisation surgery to improve ankle function and slow down development of ankle osteoarthritis [18, 21, 27].…”
Section: Introductionmentioning
confidence: 99%